Russia’s Chairmanship Programme for the Arctic Council 2021-2023 (Russian Chairmanship, 2021)
Russia builds its chairmanship of the Arctic Council on the principle of responsible governance for the sustainable development of the polar region. As a country that accounts for almost a third of the Arctic with a population of over 2.5 million people, Russia implements an integrated comprehensive development programme in the high latitudes and therefore prioritizes the balanced promotion of the region’s sustainable development in the social, economic and environmental dimensions during its 2021-2023 Arctic Council Chairmanship.